Bookstack for Teaching Materials & Practical Guidelines as Wikisource for Politala - Fitriyani, Yuli; Aristi, Nina Mia; Zulfahri, Aidil Fajar; Herpendi; Hafizd, Khairul Anwar; Fathurrahmani; Ridha, M. Najamudin (Bahasa Indonesia, 2024)
In 2023, Tanah Laut State Polytechnic (Politala) will be 14 years old since its founding. Various prestigious achievements have been achieved, including the most recent in 2021, where Politala received the best SAKIP award among all Polytechnics in Indonesia. This achievement cannot be separated from the good management of higher education by the leaders. Facing the challenges of rapidly developing digitalization, Politala continues to strive to adapt to the needs to support its vision, namely "Becoming a leading & nationally competitive Polytechnic". Politala has implemented digitalization in various aspects, one of which is in learning. They use Wikisource as an archive for storing teaching materials and practical guidelines, which are accessed by lecturers and students. However, Wikisource has limitations in managing archives, because only one admin is responsible for all existing archives. Lecturers and students can only download teaching materials and practical guidelines without adequate user access control. The implementation of Bookstack as a replacement for Wikisource in Politala is focused on increasing accessibility and user involvement with their respective roles in managing information resources. This study aims to develop Bookstack to improve the accessibility of teaching materials and practical guidelines, ease of use, and encourage active user involvement in contributing and managing content. This implementation is also expected to strengthen collaboration between users in the development and updating of teaching materials and practical guidelines. Thus, the implementation of Bookstack will increase the effectiveness and efficiency in providing teaching materials and practical guidelines in Politala, making it easier for lecturers to upload documents, and students to access them.